Tempered radicals: the outsiders within - Farnworth, Cathy Rozel (2018)
Presented by Cathy Rozel Farnworth (independent), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.